2014
DOI: 10.4028/www.scientific.net/amr.1024.136
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Graphene Nanopletelets on Poly(Lactic Acid)/Poly(Ethylene Glycol) Polymer Nanocomposites

Abstract: Graphene nanoplatelets (xGnP) were investigated as a novel nanoreinforcement filler in poly (lactic acid)(PLA)/poly (ethylene glycol)(PEG) blends by melt blending method. The prepared nanocomposites exhibited a significant improvement in tensile properties at a low xGnP loading. The tensile properties demonstrated the addition of 0.3wt% of xGnP led to an increase of up to 32.7%, 69.5% and 21.9% in tensile strength, tensile modulus and elongation at break of the nanocomposites respectively, compared to PLA/PEG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
15
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 8 publications
(9 reference statements)
9
15
0
3
Order By: Relevance
“…Figure S3A,B show the FTIR spectra of the PLA/PEG nanofilms without and with entrapped AgNPs, respectively. It can be found that the both spectrums have almost the same absorption peaks which are perfectly matched with the previous PLA/PEG FTIR reports 45,66,67 . At the same time, several slight shifts for the entrapped AgNPs sample are related to the interaction of Ag NPs with the PLA/PEG composite.…”
Section: Morphology Of Agnps Containing Nanofilmssupporting
confidence: 85%
“…Figure S3A,B show the FTIR spectra of the PLA/PEG nanofilms without and with entrapped AgNPs, respectively. It can be found that the both spectrums have almost the same absorption peaks which are perfectly matched with the previous PLA/PEG FTIR reports 45,66,67 . At the same time, several slight shifts for the entrapped AgNPs sample are related to the interaction of Ag NPs with the PLA/PEG composite.…”
Section: Morphology Of Agnps Containing Nanofilmssupporting
confidence: 85%
“…The reference spectrum is the PEG-modified surface in water. [1,6]. Moreover, the amide groups within the biotin-PEG-silane molecule ( Fig.…”
Section: Surface Passivation Of the Atr Crystalmentioning
confidence: 99%
“…Meanwhile, a broad peak was observed at 3446 cm À1 , which corresponds to the PEG terminal hydroxyl group. 19,27 PLA and plasticized PLA show almost the same absorption peaks compared to PLA, which suggests that no new bond formed had occurred when PEG was added into the PLA.…”
Section: Heat Treatment In Ovenmentioning
confidence: 93%